Fault Diagnosis Method of Planetary Gearboxes Based on LMD Permutation Entropy and BP Neural Network - Gao Sujie; Wu Shijing; Zhou Jianhua; Zheng Pan; Chen Ben; Xu Jiacai (Jixie chuandong)
In view of the problems of poor discrimination of fault feature vectors extracted in the process of fault diagnosis of planetary gearboxes and insufficient diagnosis success rate, a method based on Local Mean Decomposition（LMD） permutation entropy and BP neural network is proposed. Through the LMD decomposition of the original signal, the PF components containing the main information are obtained, and the permutation entropy values are calculated to construct the feature vector. The extracted feature vectors are used to train the BP neural network and complete the failure pattern recognition test. Taking the EMD permutation entropy method and the non-dimensional analysis method as the comparison groups, the experiment proves that the feature vectors extracted from different working conditions with this method are more distinguishable, and the fault diagnosis effect is better. Moreover, this method shows better comprehensive performance when the number of training groups changes.